Two new species of the genus Flavoperla (Plecoptera: Perlidae) from Guangxi, China - Mo, Raorao; Cao, Jinjun; Wang, Guoquan; Li, Weihai; Murányi, Dávid (Zootaxa, 2021)
Two new species, Flavoperla retusata Mo, Li & Wang, sp. nov. and F. yangi Mo, Li & Murányi, sp. nov. are proposed from the Guangxi Zhuang Autonomous Region of southern China. Distinctness of the new species is based on morphological characters and DNA sequence comparisons with their closest known relative, F. galerispina Mo, Wang & Li, 2020. The taxonomic relationships of the two new species and related congeners are discussed.